2018
DOI: 10.3390/app8122347
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Control of Ultrafast π-Electron Ring Currents in Aromatic Molecules: Roles of Molecular Symmetry and Light Polarization

Abstract: Being motivated by the recent progress in attosecond laser technology, we theoretically explore the strategy of inducing ultrafast electron dynamics inherent to aromatic molecules, i.e., ring currents by means of polarized laser pulses. The main topic of discussion is how to control the direction of ring currents in an aromatic molecule of low symmetry, for which the design of an efficient control pulse cannot be achieved intuitively. We first consider a system with a single aromatic ring and show that coheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 100 publications
(178 reference statements)
0
17
0
Order By: Relevance
“…Recent experiments realized ring-currents in ring-shaped organic chromophores with strong magnetic fields and showed that the light absorption properties of the molecules were substantially modified [1]. From a theory perspective, it is well understood that circularly polarized light can also trigger ring-currents by resonantly exciting the electrons to a manifold of doubly-degenerate electronic states of (E) symmetry related to a symmetry axis of the molecule [4,[8][9][10][11][12]. It is inevitable by symmetry, though, that the (E × e) Jahn-Teller (JT) effect couples the (E) electronic states and (e) vibrational modes in all molecular point groups able to support ring currents [13][14][15][16], thus potentially mixing the two pristine ring-current circulation directions defined in the uncoupled limit [17,18].…”
mentioning
confidence: 99%
“…Recent experiments realized ring-currents in ring-shaped organic chromophores with strong magnetic fields and showed that the light absorption properties of the molecules were substantially modified [1]. From a theory perspective, it is well understood that circularly polarized light can also trigger ring-currents by resonantly exciting the electrons to a manifold of doubly-degenerate electronic states of (E) symmetry related to a symmetry axis of the molecule [4,[8][9][10][11][12]. It is inevitable by symmetry, though, that the (E × e) Jahn-Teller (JT) effect couples the (E) electronic states and (e) vibrational modes in all molecular point groups able to support ring currents [13][14][15][16], thus potentially mixing the two pristine ring-current circulation directions defined in the uncoupled limit [17,18].…”
mentioning
confidence: 99%
“…the application of a magnetic field on a macroscopic conducting wire ring gives rise to a directional current. Despite the prevalence of ring currents in chemical systems, a detailed understanding of what effect the applied magnetic field has on molecular electronic orbitals is still an active area of investigation (24)(25)(26)(27)(28). The effects of these induced currents in aromatic organic molecules are commonly seen in NMR spectroscopy, where the induced magnetic field arising from the circular current can either enhance or detract from the Zeeman splitting of 1 H nuclei, resulting in modified chemical shifts in the NMR spectrum as compared to the absence of the ring current (29,30).…”
Section: Significancementioning
confidence: 99%
“…Also, in general, ring currents in 2D systems have an important application in optoelectronics, e.g. in design of novel optical switching devices [46,47]. The dependence of energy levels of the confined system of 2D hydrogen on the applied magnetic field and the radius of the bounding circle has been presented by us in an earlier study [48].…”
Section: Introductionmentioning
confidence: 99%